The Salai Jin Tradition as a Healing Practice of The Tubo Community - Syaiful Bahry; Syahfitri H. Sahupala; Lyra Muhisa Zalyanti; Puput Nirmala Dewi; Matrizky Adista M; Adjam Adjam; Divany Wael; Rifai Buamona; Ririn Isnawati; M. Zulfikar Umabaihi; Husnul Khatimah; Taufik Akbar (JURNAL SAINS SOSIAL DAN HUMANIORA (JSSH), 2025)
Generally, people use medical treatments, but the Tubo community has a different approach. They consider Salai Jin as a medium for healing and a prayer for the safety of their descendants. This study aims to describe the meaning of Salai Jin in Tubo Village and to identify how Salai Jin serves as a healing medium. This is a qualitative descriptive study conducted in Tubo Village, North Ternate. The subjects of the research are traditional leaders. Data collection techniques include interviews, observations, document analysis, and documentation. Interviews were conducted directly with the traditional leader in Tubo Village, followed by observations of Fala Sou, or the house believed to be the residence of the Jinn. The research findings reveal that Salai Jin signifies the summoning of spirits/jin through dance/salai for specific purposes such as healing illnesses and seeking protection and safety for their descendants. Additionally, Salai Jin was initially also understood as a ritual to fight against colonizers, as using just machetes and shields was not powerful enough. Therefore, the existence of Salai Jin provided protection.